Menyikapi Perubahan Geopolitik dan Geostrategi - Suripto (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2017)
This research aims to analyze geopolitical and geostrategic changes. Which countries have geopolitical and geo-strategic dimensions? It seems that America, Israel, Russia and China and Iran tend to have expansionist ambitions ready to compete in the global and regional arena. Russia and Iran for the time being have ambitions with regional dimensions such as Russia in Central Asia and the Middle East. While Iran is limited to the Middle East. The presence or entrenchment of global corpacy, both Corporate Capitalism and State Capitalism are considered as new forms of colonialism that must be opposed and driven out of the land of Indonesia, because the occupation of this new model will bring misery to life and will bring the fate of the younger generation and future generations to become slaves. in his own country.